Походження назв літописних слов'янських племен - Тищенко, К. (Народна творчість та етнографія, 2006)
The following article is the continuation of the research of etymology of the names of Slavonic tribes. This part presents different versions of origin of the names of such tribes as Derevlyans, Dregovyches, Drygs, Kryvyches, Radymyches, Vyatyches, Polyans, Buzhans, Ulyches, Croatians, Tyvertses and Ants.